THE CONTRIBUTION OF THE CIVIC-MILITARY MODEL TO THE PREVENTION OF VIOLENCE AND THE FORMATION OF VALUES FROM THE PERSPECTIVE OF MANAGERS, TEACHERS AND PARENTS - Claudio Sales Barbosa; Allison José dos Santos; Paulo Henrique de Assis Brazil; Danielle Farias Vitorino Brazil; Flávia Paes de Lima Siqueira (Revista Gênero e Interdisciplinaridade, 2021)
This article presents the civic-military educational model as a proposal to work on patriotic values ​​with an emphasis on the development of learning, moral and civic, aiming at an integral formation of the student. Its objective is to analyze the perceptions of teachers, parents and administrators about the contribution of the civic-military educational model to the reduction of violence, indiscipline and formation of values ​​in a city in the Metropolitan Region of Recife/PE. The methodology applied is a basic research, with a qualitative and quantitative approach, exploratory, descriptive and field. The sample consisted of 13 managers, 30 elementary and high school teachers, and 21 parents from a city in the metropolitan region of Recife/PE, who were submitted to answer an electronic questionnaire. However, this study revealed that the factors of indiscipline and violence at school have compromised students’ academic performance. The study also pointed out that ECIM, from the perspective of managers, teachers and parents, contributes to the prevention of violence in the school environment and significantly improves school performance. As well as contributing to a good academic performance. Furthermore, he highlighted that the civic-military educational model can significantly promote moral, civic and patriotic values ​​in society.